Implementation of Bonny Method of Guided Imagery and Music (BMGIM) to complement care provided in selected cancer interim homes in Gauteng province - Mulaudzi, Fhumulani Mavis (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2016.